Hard carbon material, preparation method and application thereof and lithium ion battery

By using specific types of graphite raw materials as template carbon, hard carbon materials with high disorder and appropriate pore structure are prepared, which solves the problem of insufficient capacity and performance of existing hard carbon materials, and realizes a green and environmentally friendly preparation process, which improves the capacity performance of lithium-ion batteries.

CN119774582APending Publication Date: 2025-04-08SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411981009.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing hard carbon materials have poor capacity performance in lithium-ion batteries, and the use of metal molten salt as hard templates during the preparation process can easily lead to equipment corrosion and pollution of the environment.

Method used

Using graphite oxide, redox graphite and expandable graphite as template carbon, hard carbon materials with large disorder and appropriate pore structure are prepared through pre-carbonization and carbonization treatment.

Benefits of technology

It improves the capacity performance of lithium-ion batteries, and the preparation process does not require pickling and water washing, is environmentally friendly and pollution-free, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774582A_ABST
    Figure CN119774582A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon material, a preparation method and application thereof and a lithium ion battery. The preparation method of the hard carbon material comprises the following steps: S1, carrying out pre-carbonization treatment on a mixture of a graphite raw material and a carbon source to obtain a hard carbon precursor; wherein the graphite raw material comprises one or more of graphite oxide, redox graphite and expandable graphite; the temperature of the pre-carbonization treatment is 250 to 650 DEG C; the usage amount of the graphite raw material is more than 1%, and the percentage is the mass percentage of the graphite raw material in the carbon source; and S2, carrying out carbonization treatment on the hard carbon precursor to obtain the hard carbon material, the temperature of the carbonization treatment ranges from 1000 DEG C to 1200 DEG C. The obtained hard carbon material has a relatively large disorder degree and a proper pore structure. The lithium ion battery containing the hard carbon material has excellent capacity performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon material and a preparation method, application and a lithium ion battery thereof. Background Art

[0002] The negative electrode materials of lithium-ion batteries (LIB) currently used in commercial applications are mainly graphite materials. Graphite relies on lithium ions to embed / release in its long-range ordered carbon layer to store electricity. With the continuous development of lithium-ion battery technology, higher performance requirements are also put forward for negative electrode materials. The capacity of secondary batteries using graphite materials as negative electrode materials is insufficient and cannot meet the needs of power batteries. The stability of the layered structure needs to be improved, and the rate performance is not good enough. Therefore, new materials are urgently needed as substitutes for traditional graphite materials.

[0003] Compared with graphite, hard carbon has short-range ordered and isotropic structural characteristics, with a large interlayer spacing, which can satisfy the free intercalation and deintercalation of metal ions between layers, and can also accelerate the diffusion of ions. Hard carbon materials also have the characteristics of good cycle performance and rate performance, and low cost. Therefore, hard carbon negative electrode materials have shown high capacity in secondary batteries including lithium-ion batteries and sodium-ion batteries, and have high application potential. However, most of the current solutions for the preparation of hard carbon materials are still to adjust the carbon layer structure of the material by the hard template method of metal molten salt. This method involves the use of a large amount of metal salts, which is easy to cause corrosion to the equipment; the hard template needs to be etched and washed immediately after carbonization, which will involve the discharge of acidic wastewater, polluting the environment and increasing production costs. In addition, the use of metal molten salt as a hard template is usually accompanied by difficulties in dispersion and the difficulty in accurately controlling the pore size range, which hinders the large-scale use of hard carbon in lithium-sodium negative electrode materials.

[0004] The reason for the above problems is that the hard template cannot be decomposed and overflowed at high temperature, and the residue in the hard carbon material will hinder its lithium / sodium storage behavior, resulting in poor capacity performance; and in order to remove the residual hard template, additional washing operations are required. This requires the exploration of new template materials that can adjust the structure of the hard carbon material while also playing the role of lithium / sodium storage to improve capacity performance. Summary of the invention

[0005] In order to solve the problem of poor capacity performance of lithium ion batteries obtained from hard carbon materials in the prior art, the present invention provides a hard carbon material and a preparation method, application and lithium ion battery thereof. The hard carbon material has a large disorder degree and a suitable pore structure, and a lithium ion battery containing the hard carbon material has excellent capacity performance.

[0006] To achieve the above objectives, the present invention adopts the following technical solutions.

[0007] The present invention provides a method for preparing a hard carbon material, which comprises the following steps:

[0008] S1. Pre-carbonizing a mixture of a graphite raw material and a carbon source to obtain a hard carbon precursor; wherein the graphite raw material comprises one or more of oxidized graphite, redox graphite and expandable graphite; the temperature of the pre-carbonization treatment is 250-650° C.; the amount of the graphite raw material is more than 1%, and the percentage is the mass percentage of the carbon source;

[0009] S2. Carbonizing the hard carbon precursor to obtain a hard carbon material; the temperature of the carbonization treatment is 1000-1200°C.

[0010] In the present invention, the "mixture" in the mixture of graphite raw material and carbon source refers to a solid mixture or a liquid mixture.

[0011] The present invention uses specific ordered carbons such as oxidized graphite, redox graphite and expandable graphite as template carbon. During the pre-carbonization process, the carbon source undergoes initial decomposition and chain breaking, and the template carbon plays a role at this time to induce rearrangement of the structure of the carbon source.

[0012] In the preparation method of the hard carbon material, the graphite raw material will first be oxidized to increase the disorder of the carbon source, and then it will play the role of template carbon to reduce the disorder, ultimately increasing the overall disorder of the hard carbon material.

[0013] In step S1, the amount of the graphite raw material is preferably 1%-20%, more preferably 1%-15%, for example 1%, 3%, 5%, 10% or 15%.

[0014] In step S1, the Dv50 particle size of the graphite raw material is preferably 3-15 μm, for example, 5-10 μm.

[0015] In step S1, the Dv50 particle size of the carbon source is preferably 3-15 μm, for example 5-10 μm.

[0016] In step S1, the carbon source may be a carbon source conventionally used in the art, preferably including one or more of a polymer, a biomass material, and a petrochemical product. The polymer may be, for example, a synthetic resin; the petrochemical product may be, for example, asphalt; and the biomass material may be, for example, a carbohydrate.

[0017] The synthetic resin preferably includes one or more of phenolic resin, epoxy resin, urea-formaldehyde resin, polymethyl methacrylate and polyacrylonitrile.

[0018] The asphalt preferably includes one or more of natural asphalt, coal-based asphalt, petroleum-based asphalt and oxidized asphalt.

[0019] Wherein, the carbohydrates preferably include one or more of glucose, fructose, maltose and starch.

[0020] In some embodiments, the carbon source includes one or more of phenolic resin, epoxy resin, urea-formaldehyde resin, polymethyl methacrylate, and polyacrylonitrile.

[0021] In some embodiments, the carbon source includes one or more of natural asphalt, coal-based asphalt, petroleum-based asphalt, and oxidized asphalt.

[0022] In some embodiments, the carbon source includes one or more of glucose, fructose, maltose, and starch.

[0023] In some embodiments, the carbon source is petroleum-based asphalt.

[0024] The softening point of the petroleum-based asphalt is preferably 120-150°C, for example 130°C.

[0025] Wherein, the coking value of the petroleum-based asphalt is preferably not less than 40%.

[0026] Wherein, the ash content of the petroleum-based asphalt is preferably not higher than 0.6%.

[0027] Wherein, the water content of the petroleum-based asphalt is preferably not higher than 1%.

[0028] In step S1, the preparation method of the mixture preferably comprises the following steps: crushing the carbon source, adding the graphite raw material, and mixing evenly to obtain the mixture. The crushing is preferably air flow crushing.

[0029] In step S1, the temperature of the pre-carbonization treatment is preferably 400-650°C, for example, 400°C or 650°C.

[0030] In step S1, the heating rate of the pre-carbonization treatment is preferably 0.5-5°C / min, for example, 2°C / min.

[0031] In step S1, the pre-carbonization treatment time is preferably 1-10 hours, for example, 6 hours.

[0032] In some preferred embodiments, in step S1, the pre-carbonization treatment is carried out by heating the temperature to 250-650°C at a rate of 0.5-5°C / min and then maintaining the temperature for 1-10 hours.

[0033] In some specific embodiments, in step S1, the pre-carbonization treatment is performed by heating to 400°C at a rate of 2°C / min and then maintaining the temperature for 6 hours.

[0034] In step S1, the pre-carbonization treatment device is preferably a tubular furnace or an atmosphere furnace.

[0035] In step S1, the pre-carbonization treatment may be performed in an inert atmosphere or an oxidizing gas.

[0036] The inert atmosphere preferably includes an inert gas and / or nitrogen, such as nitrogen; the inert gas is, for example, argon.

[0037] Wherein, the oxidizing gas is preferably one or more of oxygen, sulfur dioxide, nitrogen dioxide and ozone; or, the oxidizing gas is preferably air.

[0038] In step S1, the pre-carbonization treatment preferably further includes a pulverization treatment.

[0039] In step S1, the Dv50 particle size of the hard carbon precursor is preferably 3-15 μm, for example 5-10 μm.

[0040] In step S2, the temperature of the carbonization treatment is preferably 1000-1100°C, for example 1000°C.

[0041] In step S2, the heating rate of the carbonization treatment is preferably 0.5-2°C / min, for example 2°C / min.

[0042] In step S2, the carbonization treatment time is preferably 3-10 hours, for example 3 hours.

[0043] In some preferred embodiments, in step S2, the carbonization treatment is carried out by heating the temperature to 1000-1200°C at a rate of 0.5-2°C / min and then maintaining the temperature for 3-10 hours.

[0044] In some specific embodiments, in step S2, the carbonization treatment is carried out by heating the temperature to 1000°C at a rate of 2°C / min and then maintaining the temperature for 3 hours.

[0045] In step S2, the carbonization treatment device is preferably a tube furnace, an atmosphere furnace or a box furnace.

[0046] In step S2, the carbonization treatment may be performed in an inert atmosphere.

[0047] The inert atmosphere preferably includes an inert gas and / or nitrogen, such as nitrogen; the inert gas is, for example, argon.

[0048] The present invention provides a hard carbon material, which is prepared by the hard carbon material preparation method as described above.

[0049] In the present invention, the Dv50 particle size of the hard carbon material may be 3-15 μm, for example, 5-10 μm.

[0050] In the present invention, the interlayer spacing of the hard carbon material may be 0.36-0.39 nm, for example, 0.363 nm, 0.367 nm, 0.371 nm, 0.374 nm, 0.375 nm, 0.377 nm, 0.380 nm or 0.381 nm.

[0051] In the present invention, the pore size of the hard carbon material may be 0.3-0.6 nm, for example, 0.3-0.39 nm, 0.3-0.4 nm, 0.35-0.5 nm, 0.44-0.5 nm, 0.45-0.5 nm, 0.35-0.40 nm, 0.40-0.50 nm, 0.40-0.55 nm or 0.50-0.60 nm.

[0052] In the present invention, the pore volume of the hard carbon material may be 0.03-0.2 cm 3 / g, for example, 0.04 cm 3 / g, 0.05cm 3 / g, 0.06cm 3 / g, 0.07cm 3 / g, 0.08cm 3 / g, 0.10cm 3 / g or 0.11cm 3 / g.

[0053] In the present invention, the ID / IG of the hard carbon material may be 0.8-1.2, for example, 0.81, 0.83, 0.84, 0.87, 0.88, 0.90, 0.91, 0.92, 0.94, 0.98, 1.02 or 1.12.

[0054] The present invention provides the use of the hard carbon material as described above as a negative electrode material in a sodium ion battery or a sodium ion battery.

[0055] The present invention provides a lithium ion battery, which comprises the hard carbon material as described above.

[0056] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0057] The reagents and raw materials used in the present invention are commercially available.

[0058] The positive and progressive effects of the present invention are:

[0059] (1) The method for preparing the hard carbon material of the present invention uses ordered carbon such as oxidized graphite, redox graphite and expandable graphite as template carbon. The obtained hard carbon material has a large degree of disorder and an appropriate pore structure. The lithium ion battery using the hard carbon material has a high capacity.

[0060] (2) The preparation method of the hard carbon material does not require acid washing, water washing and other operations. The process is green, environmentally friendly, pollution-free and emission-free. At the same time, no hazardous chemicals such as acid and alkali are used in the production and preparation process, no waste liquid is generated, and the operation is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is the FESEM image of the hard carbon material obtained in Example 1.

[0062] Figure 2 This is the XRD pattern of the hard carbon material obtained in Example 1.

[0063] Figure 3 This is a charge and discharge performance diagram of the lithium-ion battery prepared based on the hard carbon materials SHN and SHA in Examples 1-2 of the present invention. DETAILED DESCRIPTION

[0064] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0065] Example 1

[0066] The method for preparing the hard carbon material comprises the following steps:

[0067] Step S1-1, 1000 g of block asphalt (petroleum-based asphalt, softening point 130° C., ash content ≤0.6%, moisture ≤1%, coking value ≥40%) is air-milled to a particle size of 5-10 μm, 10 g of expandable graphite (Dv50 particle size 5-10 μm) is added, and the mixture is mixed uniformly to obtain a solid mixture;

[0068] Step S1-2, placing the solid mixture in a tube furnace, introducing nitrogen at a gas flow rate of 0.1 L / min, heating to 400°C at a rate of 2°C / min, and then maintaining the temperature for 6 hours for pre-carbonization treatment; after natural cooling, the pre-carbonized material is subjected to air flow pulverization to a Dv50 particle size of 5-10 μm to obtain a hard carbon precursor;

[0069] Step S2, placing the precursor in a tubular furnace, introducing nitrogen protection, heating to 1000°C at 2°C / min, and then maintaining the temperature for 3 hours for carbonization treatment; after natural cooling, a hard carbon material (Dv50 particle size of 5-10μm) is obtained, which is recorded as SHN.

[0070] Example 2

[0071] The difference between this embodiment and embodiment 1 is that air is introduced in step S1-2 for pre-carbonization treatment. The obtained hard carbon material is denoted as SHA. The other conditions are the same as those in embodiment 1.

[0072] Example 3

[0073] The difference between this embodiment and embodiment 1 is that 150 g of expandable graphite (the content relative to the block asphalt is 15%) is added in step S1-1. The other conditions are the same as those in embodiment 1.

[0074] Example 4

[0075] The difference between this embodiment and embodiment 1 is that 50 g of expandable graphite (the content relative to the block asphalt is 5%) is added in step S1-1. The other conditions are the same as those in embodiment 1.

[0076] Example 5

[0077] The difference between this embodiment and embodiment 1 is that 100 g of expandable graphite (the content relative to the block asphalt is 10%) is added in step S1-1. The other conditions are the same as those in embodiment 1.

[0078] Example 6

[0079] The difference between this embodiment and embodiment 1 is that the temperature of the pre-carbonization treatment in step S1-2 is 250° C. The other conditions are the same as those in embodiment 1.

[0080] Example 7

[0081] The difference between this embodiment and embodiment 1 is that the temperature of the pre-carbonization treatment in step S1-2 is 650° C. The other conditions are the same as those in embodiment 1.

[0082] Example 8

[0083] The difference between this embodiment and embodiment 1 is that the temperature of the carbonization treatment in step S2 is 1200° C. The other conditions are the same as those in embodiment 1.

[0084] Example 9

[0085] The difference between this embodiment and embodiment 1 is that 200 g of expandable graphite (the content relative to the block asphalt is 20%) is added in step S1-1. The other conditions are the same as those in embodiment 1.

[0086] Example 10

[0087] The difference between this embodiment and embodiment 1 is that phenolic resin is used to replace block asphalt in step S1-1. The other conditions are the same as those in embodiment 1.

[0088] Embodiment 11

[0089] The difference between this embodiment and embodiment 1 is that in step S1-1, graphite oxide is used to replace expandable graphite. The other conditions are the same as those in embodiment 1.

[0090] Example 12

[0091] The difference between this embodiment and embodiment 1 is that redox graphite is used to replace expandable graphite in step S1-1. The other conditions are the same as those in embodiment 1.

[0092] Example 13

[0093] The difference between this embodiment and embodiment 1 is that 30 g of expandable graphite (3% relative to the content of block asphalt) is added in step S1-1. The other conditions are the same as those in embodiment 1.

[0094] Comparative Example 1

[0095] The difference between this comparative example and Example 1 is that in step S1-1, Ketjen black is used instead of expandable graphite, the mass of the conductive carbon is 10 g (relative to the content of the block pitch is 1%), and the other conditions are the same as those in Example 1.

[0096] Comparative Example 2

[0097] The difference between this comparative example and Example 1 is that 5 g of expandable graphite (the content relative to the block asphalt is 0.05%) is added in step S1-1. The other conditions are the same as those in Example 1.

[0098] Effect Example 1

[0099] (1) The hard carbon material obtained in Example 1 was tested by FESEM (field emission scanning electron microscope, manufactured by JEOL, model JSM-7800F) and XRD (X-ray powder diffractometer, manufactured by Bruker, Germany, model D8advance). The obtained FESEM and XRD patterns are shown in the figure below. Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the morphology of the hard carbon material obtained by the present invention is similar to that of conventional hard carbon materials. The present invention optimizes the performance of the hard carbon material without changing the microscopic morphology of the hard carbon material.

[0100] (2) The hard carbon materials obtained in Examples 1-13 and Comparative Examples 1-2 were tested for Dv50 particle size, interlayer spacing, pore size, pore volume and disorder. The specific testing methods are as follows:

[0101] ①Dv50 particle size: obtained by laser diffraction method using a laser particle size analyzer (Mastersizer 3000).

[0102] ② Interlayer spacing: X-ray diffractometer (D8 advance) was used to test and obtain XRD spectrum, θ was obtained according to the XRD spectrum, and the interlayer spacing d was calculated according to d=λ / 2sinθ.

[0103] ③ Pore size: Based on the nitrogen adsorption and desorption technology under the BET (Brunauer-Emmett-Teller) theory, the HK (Horvath-Kawazoe) model is adopted, and the pore size is tested using the Autosorb-iQ fully automatic specific surface area and pore size distribution analyzer.

[0104] ④Pore volume: Based on the nitrogen adsorption and desorption technology under the BET (Brunauer-Emmett-Teller) theory, the HK (Horvath-Kawazoe) model was adopted, and the Autosorb-iQ fully automatic specific surface area and pore size distribution analyzer was used to test the pore volume.

[0105] ⑤ID / IG: The Raman spectrum (Raman spectrum) is tested using a confocal Raman microscope (SENTERRAII). There are two characteristic peaks in the Raman spectrum curve, with the peak value located at 1310~1360cm -1 The peak between is the disorder peak (D peak); located at 1560~1610cm -1 The peak between the two is the graphite peak (G peak). ID / IG is obtained by the integrated area ratio of the D peak to the G peak.

[0106] The above test results are shown in Table 1.

[0107] Effect Example 2

[0108] The hard carbon materials obtained in Examples 1-13 and Comparative Examples 1-2 were used as negative electrode materials to prepare negative electrode sheets and lithium-ion batteries, and the specific steps were as follows:

[0109] (1) Preparation of negative electrode sheet:

[0110] The obtained hard carbon material is mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1, and is made into a negative electrode sheet through the operations of homogenization-coating-drying-cutting.

[0111] (2) Preparation of lithium-ion batteries:

[0112] The above-mentioned negative electrode sheet was used as the positive electrode, the lithium metal sheet was used as the negative electrode, the electrolyte was a 1 mol / L LiPF6 solution, and the solvent was a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and a CR2016 button lithium-ion battery was assembled.

[0113] The capacity performance of the lithium-ion battery prepared above was tested, and the specific test conditions were as follows:

[0114] After discharging to 0V at 0.1C rate, deep discharge at 0.02C rate (to completely release the lithium storage sites), and charging cycle at 0.1C rate, the voltage range is 0V to 2.0V. Among them, the test graphs of Examples 1 and 2 are as follows Figure 3 As shown. Figure 3 It can be seen that the discharge capacity and charge capacity of the lithium ion battery obtained by using the hard carbon material in Example 2 are higher than those of the lithium ion battery obtained by using the hard carbon material in Example 1.

[0115] The above test results are shown in Table 2.

[0116] Table 1 Some condition parameters in the preparation method of hard carbon materials and the physicochemical parameters of the obtained hard carbon materials

[0117]

[0118] Table 2 Capacity performance of lithium-ion batteries prepared from hard carbon materials

[0119]

[0120]

[0121] As shown in Tables 1 and 2, the preparation method of the hard carbon material of the present invention uses a specific type of graphite raw material as a template carbon to achieve structural rearrangement of the carbon source, and the obtained hard carbon material has a large disorder and an appropriate pore structure. Specifically, ID / IG can reach 0.81-1.12, the pore diameter can reach 0.30-0.60nm, and the pore volume can reach 0.04-0.2cm 3 / g, the interlayer spacing can reach 0.36-0.39nm, and the Dv50 particle size can reach 5-10μm. The lithium-ion battery prepared using the hard carbon material as the negative electrode material has excellent capacity performance. Specifically, the reversible capacity can reach more than 240mAh / g, and the discharge capacity can reach more than 300mAh / g.

[0122] The present invention uses a specific type of graphite raw material as the template carbon to achieve the above effect. However, whether using conductive carbon such as Ketjen black as the template carbon or the amount of the graphite raw material is too low, the above effect cannot be achieved.

[0123] Compared with Example 1, the reversible capacity and discharge capacity of the lithium ion battery prepared in Comparative Example 1 using conductive carbon such as Ketjen black to replace expandable graphite are significantly deteriorated. This may be because conductive carbon such as Ketjen black cannot effectively achieve structural rearrangement of the carbon source.

[0124] Compared with Example 1, the content of expandable graphite in Comparative Example 2 is too low, and the reversible capacity and discharge capacity of the prepared lithium-ion battery are greatly reduced.

[0125] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon material, characterized in that: It includes the following steps: S1. Pre-carbonizing a mixture of a graphite raw material and a carbon source to obtain a hard carbon precursor; wherein the graphite raw material comprises one or more of oxidized graphite, redox graphite and expandable graphite; the temperature of the pre-carbonization treatment is 250-650° C.; the amount of the graphite raw material is more than 1%, and the percentage is the mass percentage of the carbon source; S2. Carbonizing the hard carbon precursor to obtain a hard carbon material; the temperature of the carbonization treatment is 1000-1200°C.

2. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S1, the graphite raw material satisfies the following conditions a and / or b: a. In step S1, the amount of the graphite raw material is 1%-20%, more preferably 1%-15%, for example, 1%, 3%, 5%, 10% or 15%; b. In step S1, the Dv50 particle size of the graphite raw material is 3-15 μm, for example, 5-10 μm.

3. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S1, the carbon source satisfies the following conditions a and / or b: a. In step S1, the carbon source has a Dv50 particle size of 3-15 μm, for example, 5-10 μm; b. In step S1, the carbon source includes one or more of phenolic resin, epoxy resin, urea-formaldehyde resin, polymethyl methacrylate and polyacrylonitrile; and / or, the carbon source comprises one or more of natural asphalt, coal-based asphalt, petroleum-based asphalt and oxidized asphalt; Wherein, the softening point of the petroleum-based asphalt is preferably 120-150°C, for example, 130°C; Wherein, the coking value of the petroleum-based asphalt is preferably not less than 40%; Wherein, the ash content of the petroleum-based asphalt is preferably not higher than 0.6%; Wherein, the water content of the petroleum-based asphalt is preferably not higher than 1%; And / or, the carbon source includes one or more of glucose, starch, fructose and maltose.

4. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S1, the temperature of the pre-carbonization treatment is 400-650°C.

5. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S1, the pre-carbonization treatment and the hard carbon precursor satisfy one or more of the following conditions ag: a. In step S1, the heating rate of the pre-carbonization treatment is 0.5-5°C / min, for example, 2°C / min; b. In step S1, the pre-carbonization treatment time is 1-10 hours, for example, 6 hours; c. In step S1, the pre-carbonization treatment is carried out by heating the temperature to 250-650°C at 0.5-5°C / min and then maintaining the temperature for 1-10 hours, for example, heating the temperature to 400°C at 2°C / min and then maintaining the temperature for 6 hours; d. In step S1, the pre-carbonization treatment device is a tubular furnace or an atmosphere furnace; e. In step S1, the pre-carbonization treatment is carried out in an inert atmosphere or an oxidizing gas; Wherein, the inert atmosphere preferably includes an inert gas and / or nitrogen, such as nitrogen; the inert gas is, for example, argon; Wherein, the oxidizing gas is preferably one or more of oxygen, sulfur dioxide, nitrogen dioxide and ozone; or, the oxidizing gas is preferably air; f. In step S1, the pre-carbonization treatment further includes a pulverization treatment; g. In step S1, the Dv50 particle size of the hard carbon precursor is 3-15 μm, for example, 5-10 μm.

6. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S2, the carbonization treatment satisfies one or more of the following conditions af: a. In step S2, the temperature of the carbonization treatment is 1000-1100°C; b. In step S2, the heating rate of the carbonization treatment is 0.5-2°C / min, for example, 2°C / min; c. In step S2, the carbonization treatment time is 3-10 hours, for example, 3 hours; d. In step S2, the carbonization treatment is carried out by heating the temperature to 1000-1200°C at a rate of 0.5-2°C / min and then maintaining the temperature for 3-10 hours, for example, heating the temperature to 1000°C at a rate of 2°C / min and then maintaining the temperature for 3 hours; e. In step S2, the carbonization treatment device is a tube furnace, an atmosphere furnace or a box furnace; f. In step S2, the carbonization treatment is performed in an inert atmosphere: wherein the inert atmosphere preferably includes an inert gas and / or nitrogen, such as nitrogen; the inert gas is, for example, argon.

7. A hard carbon material, characterized in that: The hard carbon material is prepared by the method for preparing the hard carbon material according to any one of claims 1 to 6.

8. The hard carbon material according to claim 7, characterized in that It meets one or more of the following conditions ae: a. The Dv50 particle size of the hard carbon material is 3-15 μm, for example, 5-10 μm; b. The interlayer spacing of the hard carbon material is 0.36-0.39 nm, for example, 0.363 nm, 0.367 nm, 0.371 nm, 0.374 nm, 0.375 nm, 0.377 nm, 0.380 nm or 0.381 nm; c. The pore size of the hard carbon material is 0.3-0.6 nm, for example, 0.3-0.39 nm, 0.3-0.4 nm, 0.35-0.5 nm, 0.44-0.5 nm, 0.45-0.5 nm, 0.35-0.40 nm, 0.40-0.50 nm, 0.40-0.55 nm or 0.50-0.60 nm; d. The pore volume of the hard carbon material is 0.03-0.2 cm 3 / g, for example, 0.04 cm 3 / g, 0.05cm 3 / g, 0.06cm 3 / g, 0.07cm 3 / g, 0.08cm 3 / g, 0.10cm 3 / g or 0.11cm 3 / g; e. The ID / IG of the hard carbon material is 0.8-1.2, for example, 0.81, 0.83, 0.84, 0.87, 0.88, 0.90, 0.91, 0.92, 0.94, 0.98, 1.02 or 1.

12.

9. Use of the hard carbon material as claimed in claim 7 or 8 as a negative electrode material in a lithium ion battery.

10. A lithium ion battery, characterized in that: It comprises the hard carbon material as claimed in claim 7 or 8.

Citation Information

Patent Citations

  • Method for preparing nitrogenous graphitized hollow carbon microspheres

    CN102637533A

  • Hard carbon / graphite composite negative electrode material and lithium ion battery as well as preparation method and application thereof

    CN111244407A

  • Hard carbon material as well as preparation method and application thereof

    CN113800496A

  • Method for producing negative electrode carbon material for lithium secondary battery

    JP2001270778A

Cited By

  • Carbon negative electrode material and preparation method thereof, negative electrode plate, electrochemical device and electronic equipment

    CN121553941A